2021
DOI: 10.31729/jnma.6246
|View full text |Cite
|
Sign up to set email alerts
|

Attitude Towards Suicide among Caregivers of Patients Admitted with Suicide Attempt to a Tertiary Care Hospital: A Descriptive Cross-sectional Study

Abstract: Introduction: Understanding the attitude of caregivers towards suicide attempters could be useful in suicide prevention. The objective of this study was to study attitude towards suicide among caregivers of patients with suicide attempt admitted to a tertiary care hospital in Nepal. Methods: A descriptive cross-sectional study was conducted with 52 caregivers of patients with suicide attempt who had been admitted to a tertiary care hospital of Nepal after obtaining ethical clearance from Institutional Review C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…Fourteen studies described participants' emotional reactions (Asare‐Doku et al, 2017 ; Buus et al, 2014 ; Daly, 2005 ; Doyle et al, 2021 ; Dransart & Guerry, 2017 ; Garcia‐Williams & McGee, 2016 ; Hellerova et al, 2022 ; Ngwane & van Der Wath, 2019 ; Nosek, 2008 ; Nygaard et al, 2019 ; Talseth et al, 2001 ; Thapa et al, 2021 ; Vandewalle et al, 2021 ; Wolk‐Wasserman, 1987b ). The period following suicidal crises was described as ‘emotional turmoil’ (Daly, 2005 , p. 27), leaving carers with shock and anger at the desire of their friend or family member to end their lives (Asare‐Doku et al, 2017 ; Buus et al, 2014 ; Daly, 2005 ; Doyle et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Fourteen studies described participants' emotional reactions (Asare‐Doku et al, 2017 ; Buus et al, 2014 ; Daly, 2005 ; Doyle et al, 2021 ; Dransart & Guerry, 2017 ; Garcia‐Williams & McGee, 2016 ; Hellerova et al, 2022 ; Ngwane & van Der Wath, 2019 ; Nosek, 2008 ; Nygaard et al, 2019 ; Talseth et al, 2001 ; Thapa et al, 2021 ; Vandewalle et al, 2021 ; Wolk‐Wasserman, 1987b ). The period following suicidal crises was described as ‘emotional turmoil’ (Daly, 2005 , p. 27), leaving carers with shock and anger at the desire of their friend or family member to end their lives (Asare‐Doku et al, 2017 ; Buus et al, 2014 ; Daly, 2005 ; Doyle et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…Emphasising the magnitude of this emotional impact, one study identified post‐traumatic reactions to witnessing a suicide attempt, including re‐living the incident and emotional numbing (Ngwane & van Der Wath, 2019 ). Initial reactions gave way to ongoing stress as carers attempted to adapt to living alongside suicide risk (Buus et al, 2014 ; Daly, 2005 ; Doyle et al, 2021 ; Dransart & Guerry, 2017 ; Ngwane & van Der Wath, 2019 ; Nosek, 2008 ; Nygaard et al, 2019 ; Sellin et al, 2017 ; Talseth et al, 2001 ; Thapa et al, 2021 ; Vandewalle et al, 2021 ). Carers' persistent apprehension was described as ‘a constant concern.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The reasons for suicide attempts are various, but they may be classified into three main categories: mental diseases, social challenges, and physical conditions [13][14][15]. Depression, alcoholism, drug addiction, schizophrenia [16,17], and personality disorders have been identified as relevant risk factors for suicide attempts [18,19].…”
Section: Introductionmentioning
confidence: 99%